The multimodal approach to obesity treatment – current pharmacological and surgical methods and lifestyle changes - Kowalczuk, Maria; Lipińska, Justyna; Kopeć, Izabela; Lipiński, Łukasz; Kamiński, Jakub; Klimczak, Klaudia; Loryś, Laura; Narloch, Marcin; Kasprzak, Stanisław; Kasprzak, Karolina (Journal of Education, Health and Sport, 2024)
Introduction Obesity is one of the major health problems of today’s population and is defined as a body mass index ≥ 30 kg/m2. It is known that obesity may cause many complications such as type 2 diabetes, cardiovascular disease, osteoarthritis, obstructive sleep, apnoea, and several cancers. The only effective treatment of obesity can be pharmacological or surgical, especially when a years-long attempt to change habits has had no effects. Aim of the study This review aims to present the current state of knowledge about non-pharmacological and pharmacological obesity treatment methods. Materials and methods The paper was created based on the Pubmed database. The literature was reviewed using the keywords: ”obesity”, ”obesity treatment”, “ obesity lifestyle changes”, “obesity medications” and ”obesity surgery”. The current state of knowledge The treatment of obesity requires a multimodal approach to treatment, including the addition of anti-obesity medications or bariatric surgery, or both, to assist people in reaching and sustaining sufficient weight loss to meet treatment goals. The 3 principal components of a comprehensive lifestyle intervention are diet, physical activity, and behavioral therapy. Among available anti-obesity medications include orlistat, phentermine, topiramate, naltrexone, bupropion, liraglutide, and semaglutide. Summary The key challenge in the treatment of obesity is to maintain the effects obtained with multimodal therapy. Without proper motivation of patients and changes in eating and behavioral habits, it is impossible to achieve optimal results, therefore, in addition to medical interventions, more and more attention should be paid to psychological interventions.